Watch your tomatoes - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The tomato yellow leaf curl disease, a viral disease transmitted by whiteflies, which affected tomato cultivation in South Africa a few years ago is now spreading to neighbouring countries such as Botswana, Swaziland, Zambia and Zimbabwe. To date...